Common haplotypes of the C-reactive protein gene and circulating leptin levels influence the interindividual variability in serum C-reactive protein levels - Martínez-Calatrava, María José; González-Sánchez, José Luis; Martínez-Larrad, María Teresa; Pérez-Barba, Milagros; Serrano-Ríos, Manuel (Thrombosis and Haemostasis, 2007)
C-reactive protein (CRP) is a marker of systemic inflammation significantly associated with an increased risk of cardiovascular disease in the general population. The aim of our current work was to study those clinical and genetic variables potentially associated with interindividual variability in serum CRP levels. A random sample of 844 participants (450 women, mean age 55 years) from a study carried out on the general Spanish population (The Segovia Study) was studied. Our results showed that age, gender, waist circumference, leptin, impaired glucose tolerance and smoking were the clinical variables significantly associated with variations in serum CRP levels. Among those, leptin showed the strongest association, explaining 11% of the interindividual variability in circulating CRP levels (p < 0.001). To study the effect of genetic variants on serum CRP levels, 10 SNPs within the CRP locus were genotyped in 756 participants. Four of these SNPs (rs1417938, rs1800947, rs1130864, rs1205) were significantly associated with CRP levels after adjustment for clinical variables. Among the common haplotypes inferred from eight SNPs, two (CCATGCCT, p = 0.025; CTATCCTT, p = 0.004) explained 2.9% of the total variation in serum CRP. The results here reported show that 2.9% of the total variation in circulating CRP levels seems to be explained by genetics variations within CRP locus. Furthermore, serum leptin levels are strongly associated with serum CRP levels in our Spanish population.
Keywords: C-reactive protein; genetic; inflammation; population; leptin